GROWTH RATE OF BODY LENGTH AND HEIGHT OF MALE BALI CATTLE DURING FATTENING - Karolina Virgin Dwi Setyawati; I Putu Sampurna; Wayan Bebas (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Each organ, tissue, or body part of balinese cattle in each phase has a different speed or growth rate. The growth rate of the animal's body can be known based on the growth pattern of each body size. This study aims to determine the growth rate of male balinese cattle during fattening. The research sample used was 20 male balinese cattle from Abdi Pertiwi Livestock Farmer Group, Gerokgak, Buleleng, Bali. This study used purposive sampling method and data collection was done with saturated sampling technique. Measurements were taken once a month with three measurements as replicates for three months. The data obtained were analyzed by power regression with the equation model used is Y = aXb. The results of the power regression analysis showed a significant difference (p<0.05) in each growth rate of body length and height of male balinese cattle. The highest growth rate or has the greatest growth potential is head length, followed by neck length, body length, hip height, and shoulder height. Based on the results obtained, it can be concluded that there are significant differences in the growth rate of body length and height of male balinese cattle during fattening. Further research needs to be conducted on the growth rate of body length and height of male balinese cattle until the time the cattle are slaughtered, so that it can be known with the help of a researcher.